Factors affecting strawberry practice of highland farmers in the Royal Project Foundation - Katin Srimongkol (2018)
The objectives of this research were to study strawberry cultural practices of farmers on highland to produce high yield and quality under socio-economic conditions on highland, to study personal characteristics, socio-economic and topographic conditions affecting strawberry cultural practices, and to investigate problems and recommendations of strawberry production by farmers. Population used in this study were 41 fresh strawberry growing farmers under the Royal Project Foundation, namely, Angkhang, Intanon, Mae Hair, and Huay Nam Rin. Tools of research were questionnaires and group discussion. Statistical techniques used were percentage, maximum, minimum, standard deviation, and Pearson Product Moment Correlation (r). Hypothesis test was done by Chi - square. The findings revealed that average area for planting strawberry was 1.16 rai and most strawberry varieties (46.37 per cent) were "Pra Rachatan 70 and 50". Income from strawberry was 63,356.21 Baht with total production of 1,001.83 kg. and 787.87 kg. per rai. Farmers had received information at moderate level but most of them (56.1 percent) had extension contact with the Royal Project at maximum level. For cultural practices it was found that most farmers (97.6 per cent) had standardized land preparation, good soil preparation (92.7 per cent), no herbicide before planting but using hoe instead (63.4 per cent), using green manure and organic fertilizer (90.2 per cent), no planting at fixed time (63.4 per cent), using runners with moderate quality (48.8 per cent), using pesticide according to extension agent's device (92.7 per cent), picking up strawberry 7 days after spraying (68.3 per cent), and grading and packaging as advised by the Royal Project (95.1 per cent). As for hypothesis testing, it was found that ethnic group was significantly related to pre-planting herbicide and harvest after spraying at 0.05 level. Farmers who lived longer in the village had proper cultural practices more than those who lived sooner. Based on group discussion, it was found that traditions and custom were not associated with cultural practices at all. As for problems, obstacles and recommendations advocated by farmers, it was found that farmers faced with natural disaster, improper soil preparation, imperfect soil conditions, uncompleted and imperfect runners, insufficient water sources, delay planting, no chemical residue checking, labor shortage during harvesting and improper size of tray for packaging. It was recommended that organic fertilizer should be applied. Sufficient runners at ready time should be prepared and packaging should be improved.